REVIEW ON FORMULATION AND EVALUATION OF SUSTAIN RELEASE TABLET USING NATURAL POLYMER - Gunjan Singh; Narendra Gehalot; Vikas Jain (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The review focuses on the formulation and evaluation of sustained release tablets using natural polymers. The sustained release (SR) dosage forms are designed to release drugs over extended periods, improving therapeutic efficacy and patient compliance. The paper discusses the advantages and limitations of sustained release tablets, methods of preparation, and various natural polymers used in these formulations. Natural polymers such as chitosan, starch, cellulose, xanthan gum, guar gum, locust bean gum, and gum karaya have been highlighted for their roles in enhancing drug release profiles. The review also covers evaluation tests for sustained release tablets, including thickness, diameter, weight variation, hardness, friability, content uniformity, and in-vitro dissolution tests. The findings indicate that sustained release tablets, particularly those using natural polymers, offer significant benefits over conventional dosage forms in terms of controlled drug delivery and patient adherence.